Asymptotics of solutions of discontinuous singularly perturbed boundary-value problems - Mel'nik, T. A. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We construct an asymptotic expansion of a boundary-value problem for a singularly perturbed system of differential equations with the right-hand side discontinuous at certain surface.